(untitled) - Zenoff, David B. (Englewood Cliffs, N.J., 1969)
The book is intended to supplement standard texts on economic developmet, international business management, and public sector policy-making for university students, faculty, and professionals in such disciplines as economic, business administration and public administration.
Keywords: Investments, Foreign,Developing countries,Đầu tư nước ngoài,Các nước đang phát triển; Developing countries,Commerce,Các nước đang phát triển,Thương mại